Assessment of Relationships Between Joint Motion Quality and Postural Control in Patients With Chronic Ankle Joint Instability - Bączkowicz, Dawid; Falkowski, Krzysztof; Majorczyk, Edyta (The journal of orthopaedic and sports physical therapy, 2017)
Study Design Controlled laboratory study, cross-sectional. Background Lateral ankle sprains are among the most common injuries encountered during athletic participation. Following the initial injury, there is an alarmingly high risk of reinjury and development of chronic ankle instability (CAI), which is dependent on a combination of factors, including sensorimotor deficits and changes in the biomechanical environment of the ankle joint. Objective To evaluate CAI-related disturbances in arthrokinematic motion quality and postural control and the relationships between them. Methods Sixty-three male subjects (31 with CAI and 32 healthy controls) were enrolled in the study. For arthrokinematic motion quality analysis, the vibroarthrographic signals were collected during ankle flexion/extension motion using an acceleration sensor and described by variability (variance of mean squares [VMS]), amplitude (mean of 4 maximal and 4 minimal values [R4]), and frequency (vibroarthrographic signal bands of 50 to 250 Hz [P1] and 250 to 450 Hz [P2]) parameters. Using the Biodex Balance System, single-leg dynamic balance was measured by overall, anteroposterior, and mediolateral stability indices. Results Values of vibroarthrographic parameters (VMS, R4, P1 and P2) were significantly higher in the CAI group than those in the control group (P<.01). Similar results were obtained for all postural control parameters (overall, anteroposterior, and mediolateral stability indices; P<.05). Moreover, correlations between the overall stability index and VMS, and P1 and P2, as well as between the anteroposterior stability index and P1 and P2, were observed in the CAI patient group, but not in controls. Conclusion In patients with CAI, deficits in both quality of ankle arthrokinematic motion and postural control were present. Therefore, physical therapy interventions focused on improving ankle neuromuscular control and arthrokinematic function are necessary in CAI patient care. J Orthop Sports Phys Ther 2017;47(8):570-577. Epub 4 Nov 2016. doi:10.2519/jospt.2017.6836.